Images of death and dying in ISIS media: A comparison of English and Arabic print publications. (September 2019) - Winkler, Carol; ElDamanhoury, Kareem; Dicker, Aaron; Lemieux, Anthony F
Images of death and dying in the media around the globe have a symbiotic relationship with nation states as they can bolster state control by defining who has the right to take lives in the interests of the community, by identifying enemies of the state, by demonstrating dominance over enemies, and by lending a moral posture to the state's war efforts. Previously, the growing corpus of research on media's display of death and about to die images has focused almost exclusively on media outlets that bolster established states on the global stage. By analyzing 1965 death and about to die images displayed in Dabiq, ISIS's English-language magazine, and al-Naba', the same group's Arabic-language newspaper, this study adds an understanding of the messaging strategies deployed by groups striving to challenge, rather than reinforce, existing national boundaries. The findings suggest that while ISIS adopts some standard media practices, it also utilizes unique and audience targeted approaches regarding the frequency of image use, the identify of the corpses, the display of dead bodies, and the presentation of those responsible for the pictured dead bodies in its media campaign.